IMPLEMENTASI METODE EXTREME PROGRAMMING PADA APLIKASI PELAYANAN PUBLIK KEWASPADAAN NASIONAL DAN PENANGANAN KONFLIK KESBANGPOL KOTA MANADO - Kristofel Santa; Rafter Johanes Karouw (Journal of Innovation And Future Technology, 2025)
The development of information technology has had a significant impact on various aspects of life, including governance and public services. In this digital era, the use of information technology has rapidly increased, enabling the creation of good governance through transparency and accountability. In Manado City, the National Unity and Politics Agency (Kesbangpol) has a mission to provide fast, accurate, and friendly services to the community. However, limitations in human resources and manual archiving sistems have led to delays in issuing activity recommendation letters and difficulties in data management. To address these issues, it is necessary to develop the "Application for National Vigilance and Conflict Management Services at Kesbangpol Manado City." The method to be used in developing this application is Extreme programming (XP). The XP method is highly relevant as it focuses on team collaboration, rapid feedback, and iteration, allowing for adaptive and responsive software development that meets user needs. With this approach, the team can quickly respond to changes in requirements and improve features based on user input, ensuring that the resulting application is not only efficient but also aligned with user expectations. It is hoped that this application will enhance the efficiency of managing recommendation letters and simplify the monitoring and evaluation processes, thus enabling public services to be delivered in accordance with established standards.